Evaluation and improvement of dehydrogenation conversion and isomerization selectivity in an extractor Catalytic Membrane Reactor - Van Dyk, Lizelle Doreen (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Process Engineering))--University of Stellenbosch, 2006.